A "Lamellar structure" contributes to autophagosome biogenesis and mitophagy in zebrafish hepatocytes. Issue 81 (October 2018) - Huang, Yufei; Yang, Ping; Chen, Hong; Bai, Xuebing; Wang, Xindong; Vistro, Waseem Ali; Haseeb, Abdul; Shi, Yonghong; Chen, Qiusheng
Abstract: Despite many studies being conducted over the past few decades, the origin of autophagosomal membranes remains unclear. The present study aimed to uncover the formation process of autophagosomal membranes in hepatocytes of zebrafish ( Danio rerio ), a model organism in medical science. Immunohistochemistry of zebrafish hepatocytes indicated that light chain 3-like protein 2 (LC3-II) is highly active in some hepatocytes, but poorly expressed in others. Under transmission electron microscopy, the amount of autophagosomes (APs) varied in different hepatocytes. When the endoplasmic reticulum (ER) is dispersed in the cytoplasm, few isolation membranes (IMs) and APs were observed. Subsequently, when the ER assembles into a particular "lamellar structure" (LS), IMs arise from it and extend to enwrap the mitochondria. With further aggregation of the ER, the LS developed into an over twenty-layered structure, and mitophagy was more obvious in the hepatocytes and cavities appeared in mitochondria. Finally, most ERs were assembled into several LSs. At this point, mitophagy was most active in the hepatocytes. Thereafter, glycogen and lipid droplet increased gradually, while the LS degenerated and ER scatter increased. Then, the glycogen and lipid droplets dominated the hepatocellular cytoplasm. After suppressing the formation of autophagosomes using 3-Methyladenine (3-MA), the LS could no longer be visualized in the hepatocellular cytoplasm, and mitophagy decreased drastically. Taken together, the results suggested that this LS in the hepatocytes of zebrafish, might be another manifestation of a pre-autophagosomal structure in zebrafish liver, analogous to the omegasome in yeast or the ER-IM complex in mammalian cell lines. Furthermore, selective mitophagy and consequent cyclic utilization of its products were probably relevant to dynamic cycle of the hepatocellular cytoplasm. Highlights: Lamellar Structure might be pre-autophagosomal structure in zebrafish hepatocytes. Isolation Membranes mainly develop from Lamellar Structure. Selective mitophagy promotes dynamic cycle of the hepatocellular cytoplasm.